Ethnic Harmony in Islamic Higher Education: Building Religious Moderation in Aceh's Private Islamic Religious Universities - Sandra, Aria; Rahmalia, Tgk. Lina; Rijal, Fakhrul; Furqan, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Ethnic harmony is a significant challenge in the context of religious and cultural diversity, especially in regions with abundant ethnic and cultural wealth such as Aceh. Private Islamic religious universities in Aceh have a crucial role in facilitating inter-ethnic dialogue and promoting religious moderation as a foundation for ethnic harmony. Based on this, this study is interesting for further study in promoting religious moderation and building inter-ethnic harmony. This study uses a qualitative descriptive analysis model with a phenomenological approach as a framework and analytical method. Data sources consist of secondary and primary data obtained through in-depth interviews with lecturers and students from research subjects. The findings show that private Islamic religious universities in Aceh have a role in facilitating inter-ethnic dialogue and promoting religious moderation as a foundation for ethnic harmony. Through educational programs and extracurricular activities, as well as the establishment of the Religious Moderation House (RMB), the college provides space for open discussions about religious and cultural differences, encourages inclusive attitudes, and broadens cross-cultural horizons among students.